An analysis of two performing actions as social intervention tools for the prevention of gender violence (Sustainability in Debate, 2014)
The work presented here was developed in a PhD research. We chose two performative actionscarried out in the context of prevention projects of gender violence in Porto between 2009 and2010, articulated with formal educational processes, non-formal and informal. The actions underreview are as follows: 1: Cry for Justice; 2: Traffic of human beings Visual analysis within theframework of cultural anthropology was our methodological choice, putting up an improvisationalapproach to the film, a mix of film essays taken from the immediate social and cultural contextand involved in a detached situation of their daily lives. Also we seek to consistently articulatethe link between art as a means of social transformation and the debate on sustainability. Weconsider that the objective has been achieved, since the audience participated by showinginterest and actions we felt, still, he was impressed by these problems.